2014
DOI: 10.1186/1471-230x-14-82
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific prevalence of serrated lesions and their subtypes by screening colonoscopy: a retrospective study

Abstract: BackgroundSerrated lesions of the colorectum as categorized by pathology include hyperplastic polyps, sessile serrated adenomas without dysplasia, and traditional serrated adenomas with dysplasia. The aim of this study was to investigate the prevalence of various subtypes of serrated lesions by age.MethodsIn this study, 28,544 consecutive asymptomatic patients (aged 22–88 years) were evaluated during health check-ups involving colonoscopies performed by gastroenterologists at a single institution from 2005 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 21 publications
7
31
0
4
Order By: Relevance
“…The current subgroup analysis also shows that the beneficial effect of NSAIDs was observed in both sex, but may be higher in females. However, it was only significant among those aged 60 years or above, which may be explained by lower burden of both adenomatous and serrated polyps in younger patients, and hence a lower risk of missed colonic polyps or incomplete resection of lesions. The beneficial effect of NSAIDs was also limited to nondiabetic patients and those without the history of colonic polyps.…”
Section: Discussionmentioning
confidence: 93%
“…The current subgroup analysis also shows that the beneficial effect of NSAIDs was observed in both sex, but may be higher in females. However, it was only significant among those aged 60 years or above, which may be explained by lower burden of both adenomatous and serrated polyps in younger patients, and hence a lower risk of missed colonic polyps or incomplete resection of lesions. The beneficial effect of NSAIDs was also limited to nondiabetic patients and those without the history of colonic polyps.…”
Section: Discussionmentioning
confidence: 93%
“…It has been presented from previous studies that serrated lesion development slightly increases with age [11][12][13], and in a recent study from Kim et al in 2014, it was concluded that SSA/Ps tend to occur more frequently in younger patients (<50) than conventional adenomas [12]. In our study, it was found that age is a risk factor for developing SSA/Ps especially after the age of 50 comparing to normal population and also that SSA/Ps seem to have their peak incidence 10 years earlier than that of conventional adenomas [51-60 p=0.001 and 61-70 (p=0.001), respectively].…”
Section: Discussionmentioning
confidence: 99%
“…This is also consistent with our animal model for serrated neoplasia where we observe a slow accumulation of DNA methylation changes over time, however these are dramatically accelerated by mutating BRAF, congruent with development of serrated neoplasia (32). This may explain why BRAF mutant sessile serrated adenomas are often identified in younger patients, despite the cancers arising from them occurring primarily in older patients (12, 33, 34). Understanding the role of age-related methylation might inform surveillance for younger patients with sessile serrated adenomas.…”
Section: Discussionmentioning
confidence: 99%